The Effect of Dhikr and Mental Tranquility Based On a Psychological Perspective - Anati Rahila (Feelings: Journal of Counseling and Psychology, 2025)
Restlessness of the heart, anxiety and distress are human feelings that can be felt by all human beings. These feelings, of course, can disturb someone. Bad feelings that arise can be caused by traumatic experiences or others. A person will continue to seek peace of mind to relieve these disturbing feelings. One of the efforts that can be done by every human being in improving peace of mind is by dhikr. Dhikr itself can be broadly interpreted as a form of a servant in remembering his God. Based on several previous studies that researchers have summarized, it was found that dhikr has a good influence on increasing the peace of mind of a person based on Islam. Dhikr has a strong connection with one's soul. By dhikr one will continue to remember God and feel better. This research uses qualitative research methods with literature study data sources in the form of scientific journals, previous research, documents, magazines, newspapers and books with related problems. This study aims to determine how the influence of dhikr and mental tranquility based on a psychological perspective. This study found that dhikr has a positive influence on increasing one's mental tranquility. Dhikr can be used as a method of psychological treatment for individuals who are experiencing traumatic, facing certain problems or pressures.